1995
DOI: 10.1039/dt9950003721
|View full text |Cite
|
Sign up to set email alerts
|

L-Methionine increases the rate of reaction of 5′-guanosine monophosphate with the anticancer drug cisplatin: mixed-ligand adducts and reversible methionine binding

Abstract: L-Methionine (L-HMet) increased the rate of reaction of the anticancer drug cisplatin, cis- [PtCI,(NH,),], with guanosine 5'-monophosphate (5'-GMP) at pH 7. The course of the reaction has been elucidated by 'H and ['H, 15N] N M R spectroscopy. Novel intermediates detected and characterized include cis-[ Pt(Y-GMP-W) ( L-H Met-S) ( NH,),I2+ and [Pt( L-Met-S,N) (5'-GMP-W ) ( NH,)] + (charges on 5'-GMP ignored), the formation of which involves ammine release. Monodentate S-bound L-H Met can co-ordinate reversibly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 14 publications
(2 reference statements)
7
53
1
Order By: Relevance
“…However, from the differences in sequence-dependent binding rates of the hydrolysis products of cisplatin to double-stranded oligonucleotides, it has been concluded that the diaqua and/or the aqua/ hydroxo complex resulting from hydrolysis of both chloro ligands rather than the chloro/ aqua complex seems to be the major species interacting with DNA in vivo (Kozelka et al 1999;Legendre et al 2000). Entirely different, hydrolysis-independent routes to DNA adduct formation involving intermediates with reversibly bound thioether ligands have been proposed based on the observation that methionine (Barnham et al 1995b) and other thioether ligands (van Boom et al 1999) bound monodentally to the platinum centre may be exchanged for GMP (for a review see Reedijk 1999). However, the following recent findings argue against the assumption that such pathways of DNA platination contribute significantly to the tumour-inhibiting activity of cisplatin: thioether-containing intermediates bind to oligonucleotides with rather slow kinetics , while replacement of thioether ligands by thiol-containing ligands in the presence of the latter proceeds much faster and results in species which appear unlikely to serve as intermediates due to their high stability .…”
Section: The First Generation -Cisplatinmentioning
confidence: 97%
“…However, from the differences in sequence-dependent binding rates of the hydrolysis products of cisplatin to double-stranded oligonucleotides, it has been concluded that the diaqua and/or the aqua/ hydroxo complex resulting from hydrolysis of both chloro ligands rather than the chloro/ aqua complex seems to be the major species interacting with DNA in vivo (Kozelka et al 1999;Legendre et al 2000). Entirely different, hydrolysis-independent routes to DNA adduct formation involving intermediates with reversibly bound thioether ligands have been proposed based on the observation that methionine (Barnham et al 1995b) and other thioether ligands (van Boom et al 1999) bound monodentally to the platinum centre may be exchanged for GMP (for a review see Reedijk 1999). However, the following recent findings argue against the assumption that such pathways of DNA platination contribute significantly to the tumour-inhibiting activity of cisplatin: thioether-containing intermediates bind to oligonucleotides with rather slow kinetics , while replacement of thioether ligands by thiol-containing ligands in the presence of the latter proceeds much faster and results in species which appear unlikely to serve as intermediates due to their high stability .…”
Section: The First Generation -Cisplatinmentioning
confidence: 97%
“…However, these bridged complexes are unlikely to be reactive towards DNA bases, although the ammine complexes can slowly release ammonia. [29,30] Reactions carried out with [PtCl(dien)]Cl and methionine (Met) or methylated glutathione (GSMe) [26,27] and 5Ј GMP have indicated that the platinumϪsulfur adducts [Pt(dien)(Met-S)] 2ϩ and [Pt(dien)-(GSMe-S)] 2ϩ are formed initially with subsequent intermolecular displacement of the thioether in the PtϪS adducts by 5Ј GMP-N7. Interestingly, this displacement of guanine-N7 has been observed only with thioether adducts and not for reactions with thiolate complexes.…”
Section: Introductionmentioning
confidence: 99%
“…92, 93 In contrast to the reversibility of thioether binding, glutathione is not readily displaced from Pt(II) by nucleotides. MT is another target with a high affinity for Pt(II); it has the ability to react directly with cisplatin without preliminary hydrolysis to the aqueous species.…”
Section: -88mentioning
confidence: 99%